E-Commerce's Impact On Economic Growth - Anggraeni, Lidya; Tan, Syamsurijal; Junaidi, Junaidi; Achmad, Erni (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the impact of e-commerce on economic growth in Indonesia using a Systematic Literature Review (SLR) approach. E-commerce has become a significant global phenomenon, and Indonesia is projected to have the highest e-commerce growth rate in the world in 2024. With an e-commerce trade value reaching 78%, Indonesia shows great potential in this sector. The study finds that e-commerce contributes significantly to increased productivity and efficiency, broader market access, and technology and innovation adoption by SMEs. However, challenges such as technology access, digital literacy, and infrastructure remain obstacles. The study emphasizes the need for policies that support the enhancement of digital infrastructure and training for SMEs to optimize e-commerce potential. Relevant policy implications can help the government and stakeholders maximize the benefits of e-commerce for national economic growth. By using the SLR approach, this study provides a comprehensive and integrative analysis of the impact of e-commerce on economic growth in Indonesia and presents strong empirical evidence of the causal relationship between the two. The study also offers recommendations for future research, including the use of primary data, regional analysis, international comparative studies, and attention to social and environmental impacts. Additionally, further research into policy and regulatory effectiveness, the role of technology and innovation, longitudinal studies, and collaboration with the private sector is also recommended. Thus, this study makes an important contribution to understanding and leveraging e-commerce potential for sustainable economic growth in Indonesia.